(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
A column is a straight-mounted element that starts from the ground and transfers various loads to the foundation. Similarly, floating columns are direct entities that are fixed units at the lower level of the support, called the fixed section. There are a number of planned projects that use fluting columns especially the ground and beam.to provide additional free space on the ground floor SAP2000 software is used to perform the exam of the generally constructed structures. Modal have a look at, reaction spectrum research and time history study are completed on numerous organized fashions by changing the position of the floating column from first ground to top floor. In a response spectrum case, for a given route of acceleration, the maximum forces, stresses, and displacements were calculated at some point of the shape for each and every mode of the vibration. These modal results for a given response amount are mixed to yield a unmarried, wonderful outcome for the given specific path of acceleration using someone of the modal mixture processes. The effects are calculated and an evaluation is made amongst this model.